ANALISIS YURIDIS PENYELESAIAN PERSELISIHAN INTERNAL PARTAI POLITIK OLEH MAHKAMAH PARTAI DI DINDONESIA - FEBRI RAMADHANI (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
This study aimed to analyze the existence of a party tribunal in resolving internal political party disputes under the provisions of law number 2 of 2011 concerning Amandements to Law Number 2 of 2008 regarding Political Parties. Its existence is designed as an internal tribunal to quickly examine and decide cases of internal party disputes with certainty and justice. However, party tribunals and the decisions made have yet to be able to assist political parties in resolving disputes efficiently and effectively. This study used normative legal research metods with a statutory, case, and conseptual approaches. The results of this study indicate that the internal dispute resolution mechanisms of political parties are carried out through the political party tribunal. Suppose a settlement through the political party tribunal has yet to be reached. In that case, the settlement of political party disputes is carried out through the District Tribunal, and it can be followed by filing an appeal to the Supreme Court. Arrangements related to internal conflicts must be regulated more clearly in the law to create democratic regulations and uphold the principle of legal certainty.